Efficient and Rapid Synthesis of Radioactive Gold Nanoparticles by Dielectric Barrier Discharge. (12th December 2016) - Bouchard, Mathieu; Laprise‐Pelletier, Myriam; Turgeon, Stéphane; Fortin, Marc‐André
Abstract : A compact bench‐top system based on a dielectric barrier plasma discharge (DBD), enables the rapid, automatable, and continuous‐flow synthesis of gold nanoparticles (AuNPs) and radioactive gold nanoparticles ( 198 AuNPs). AuNPs are used as radiosensitizers in oncology, and 198 AuNPs (half‐life: 2.7 d) have been suggested as potential cancer brachytherapy sources. Plasma applied at the surface of a liquid containing gold ions (AuCl4 − ) and dextran induces the production of AuNPs directly in water. This synthesis is monitored in real time by UV–visible spectrometry: the change of absorbance of the solution provides new insights on the growth dynamics of AuNPs by plasma synthesis. By balancing gold ions and surfactant molecules, particles with a diameter lying in the optimal range for radiosensitizing applications (28 ± 9 nm) are produced. The method yields a reduction of more than 99% of the gold ions within only 30 min of plasma treatment. A postsynthesis ripening of the AuNPs is revealed, monitored by UV–visible spectrometry, and quantified within the first few hours following plasma treatment. Radioactive 198 AuNPs are also produced by DBD synthesis and characterized by electron microscopy and single‐photon emission computed tomography imaging. The results confirm the efficiency of DBD reactors for AuNPs synthesis in oncology applications. Abstract : A compact bench‐top system based on a dielectric barrier plasma discharge enables the rapid, automatable, and continuous‐flow synthesis of radioactive gold nanoparticles for radiotherapy applications. This synthesis takes place directly in water, and is monitored by UV–visible spectrometry. The nanoparticles are characterized by electron microscopy, dynamic light scattering, and nuclear imaging, revealing new insights on their growth dynamics.